Nintendo Wii Game in Balance Stroke Rehabilitation: A Narrative Review - Javid Mostamand; Ehsan Ghasemi; Narges Yousefi (مجله پژوهش در علوم توانبخشی, 2020)
Introduction: Stroke is known as the second cause of disability in adults, which finally leads to disabilities such as movement impairments, cognitive disorders, and speech disorders. Balance disturbance and neuromuscular incoordination are the most common adverse effects of stroke. Using virtual reality systems are considering as a standard treatment method in neurologic disorders especially in stroke. Nintendo Wii games let patients do different tasks in miscellaneous environment.